2002
DOI: 10.1039/b207944e
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase detection of tributyltin chloride arising from aqueous and solid matrices

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Gas phase detection of tributyltin chloride arising from aqueous and solid matrices Bancon-Montigny, C.; Maxwell, P.; Yang, L.; Mester, Z.; Sturgeon, R.; Lam, J.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le site LISEZ CES CONDITIONS ATTENTIVEMENT AVANT D'UTILISER CE SITE WEB. NRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…275 No reagents were required and calibration was achieved by use of CRM-based external calibration. The volatile butyltin species in the headspace above solid sediments was characterized as chlorides by GC-electron impact MS and capillary GC-negative ion chemical ionization MS. 276…”
Section: Snmentioning
confidence: 99%
“…275 No reagents were required and calibration was achieved by use of CRM-based external calibration. The volatile butyltin species in the headspace above solid sediments was characterized as chlorides by GC-electron impact MS and capillary GC-negative ion chemical ionization MS. 276…”
Section: Snmentioning
confidence: 99%
“…Studies using solid phase microextraction have shown 31 that tributyltin chloride is sufficiently volatile at room temperature to be sampled from the headspace above saline water, and determined by GC-MS. This work indicates two important findings: that TBT-Cl can be lost from water samples unless they are stored below room temperature; and that the evaporation of TBT-Cl is an important biogeochemical mechanism for the butyltin compounds commonly found in the marine environment.…”
Section: Water Analysismentioning
confidence: 99%
“…The same authors 119 have also described a similar method employing ID in combination with HPLC-ICP-MS detection for the same analytical task. Bancon-Montigny et al 31 demonstrated that TBT chloride could be detected in the vapour phase above PACS-2 sediment after one night of passive sampling, without any heating of the sample. This observation was exploited by Scriver et al, 118 who developed a technique based on in situ trapping of TBT as the volatile chloride using flow injection coupled to ETAAS, after microwave-assisted leaching and continuous purging of the TBT chloride through a gas-liquid separator.…”
Section: Speciation Studiesmentioning
confidence: 99%
“…The direct determination of TBT without derivatization has been reported. 375 The TBT in the headspace above aqueous and solid samples was collected using a SPME fibre and desorbed thermally directly into a GC port. Treatment of the GC capillary column with a dilute HBr solution to deactivate sites in the GC column allowed direct injection of the sample species to be made.…”
Section: Gas Chromatography-electron Ionization Mass Spectrometry (Gc...mentioning
confidence: 99%